Arterial Doppler Waveforms Are Independently Associated With Maximal Walking Distance in Suspected Peripheral Artery Disease Patients - Miossec, Annaïg; Tollenaere, Quentin; Lanéelle, Damien; Guilcher, Antoine; Métairie, Antoine; Le Pabic, Estelle; Carel, Awenig; Le Faucheur, Alexis; Mahé, Guillaume (Frontiers in Cardiovascular Medicine, 2021)
Objective: Arterial Doppler waveform recordings are commonly used to assess lower extremity arterial disease (LEAD) severity. However, little is known about the relationship between arterial Doppler waveform profiles and patients' walking capacity. The purpose of this study was to assess whether arterial Doppler waveforms are independently associated with maximal walking distance (MWD) in patients experiencing exertional limb symptoms. Materials and Methods: This cross-sectional study included suspected LEAD patients experiencing exertional limb symptoms. In both lower extremities, arterial Doppler waveforms and ankle-brachial index (ABI) values were obtained from the pedis and tibial posterior arteries. Each arterial flow measurement was ranked using the Saint-Bonnet classification system. Treadmill stress testing (3.2 km/h, 10% slope) coupled with exercise oximetry (Exercise-TcPO2) were used to determine MWD. Delta from rest oxygen pressure (DROP) was calculated. Following treadmill stress testing, post-exercise ABI values were recorded. Univariate and multivariate analyses were used to determine the clinical variables associated with MWD. Results: 186 patients experiencing exertional limb symptoms (62 ± 12 years and 26.8 ± 4.5 kg/m2) were included between May 2016 and June 2019. Median [25th; 75th] treadmill MWD was 235 [125;500]m. Better arterial Doppler waveforms were associated with better walking distance (p = 0.0012). Whereas, median MWD was 524 [185;525]m in the group that yielded the best Doppler waveforms, it was 182 [125,305]m in the group with the poorest Doppler waveforms (p = 0.0012). MWD was significantly better (p = 0.006) in the patients with the best ABIs. However, arterial Doppler waveforms alone were significantly associated with MWD (p = 0.0009) in the multivariate model. When exercise variables (post-exercise ABI or DROP) were incorporated into the multivariate model, these were the only variables to be associated with MWD. Conclusion: Of the various clinical parameters at rest, Doppler flow waveform profiles were associated with MWD in suspected LEAD patients. A stronger link was however found between exercise variables and MWD.